Migration among Farmers in Delta State, Nigeria: Is it a Climate Change Adaptation Strategy? - Albert Ukaro Ofuoku; Davina Okompu (Journal of Agriculture and Environment for International Development)
Objective: The study has the purpose of evaluating the nexus between climate change and migration of farmers in Delta State, Nigeria. The influence exerted by cognitive situations and climate – driven stress on farmers’ decisions to migrate and the socioeconomic attributes of migrating and non-migrating farm families are examined. The emphasis is the function of migration in accessing climate and agricultural extension services as well as the contribution made by migration to promote farmers’ climate change coping capacity. Methodology: Survey was articulated using farming households in three agricultural zones of Delta State, Nigeria. Perceptions of farmers about alterations in climate were examined with the use of mental map technique. Binary logistic regression model was applied to assess the function of socioeconomic attributes of farm families while descriptive statistics was employed in evaluating the adaptive capacities of the migrating farming households. Findings: Climate – driven livelihood variables form part of the main propellers of migration among farmers. Migration as well as the socioeconomic attributes is influenced by perception of farmers about climate change. There appears significant difference between migrating and non-migrating farm families with respect to utilization of information, technology and knowledge emanating from agricultural and climate extension services. The gains from remittances, knowledge and social networks from host communities or zones raise migrating farm families capacity to adapt to climate change. Theoretical Implications: This paper contributes to the progressively dynamic body of knowledge by pointing out migration as an alternative climate change adaptation strategy to promote agriculture food security in any part of the world. Originality/Value: Micro – evidence is offered by this study with respect to contribution made by migration to adaptive capacity of farmers and their ability to have access to agricultural and climate extension services. This will be useful in the analysis of climate – driven migration in other nations that are agricultural economies. Insight is also offered regarding policy needs for the scaling down of farmers’ vulnerability to climate change.